Characterization of gastric problems in users of a hospital in Huancavelica, Peru - Nieva-Villegas, Lilia Maria (2020)
Objective. To characterize the gastric problems of user population of the Regional Hospital of Huancavelica Zacarias Correa Valdivia in the years 2015-2017. Method. It is a descriptive, cross-sectional, non-experimental, retrospective and bibliographic study, with a bibliographic review of the Health Information System (HIS) and medical records of patients treated with gastric problems in the years mentioned (n = 3261). Results. It was evidenced that 67% of the population are women. 34.7% were born in the Huancavelica region. 93.7 % had office work. 78.1% were users of the gastroenterology service. 93.7 % did not report their discharge status. 34.5 % did not have a health insurance system, and 61.7 % of the population suffered from nonspecific chronic gastritis. Patients diagnosed with gastric problems represented 64.9% of cases in 2015, 55.4% in 2016 and 64.3% of total consultations in 2017. Conclusion. Women presented the highest frequency of diagnosis of chronic non-specific gastritis, as well as young people and young adults for the year 2017 according to the total number of diagnoses retrospectively observed in the HIS report